WAYS TO IMPROVE LEADERSHIP SUCCESS FACTORS IN IMPLEMENTING INNOVATIVE IDEAS (International Conference on Economics, Finance, Banking and Management, 2025)
This article analyzes the issues of improving the success factors of leadership in implementing innovative ideas. The study studies the effectiveness of managing innovation processes based on modern concepts of leadership - transformational, strategic and innovative leadership approaches. Also, special attention is paid to the role of leaders in creating an innovative environment in organizations, stimulating creativity and supporting employee initiative. Based on the analysis of the experience of foreign countries, scientific and practical proposals for developing leadership skills and improving innovative management in the conditions of Uzbekistan have been developed.